PELAYANAN PUBLIK LEGALISASI TANAH BERDASARKAN INSTRUKSI PRESIDEN (INPRES) NOMOR 2 TAHUN 2018 TENTANG PERCEPATAN PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KOTA PEKANBARU TAHUN 2021 - Sanggam Fernando Naibaho; Zulfa Harirah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Complete Systematic Land Registration (PTSL) is one of the national priority programs for asset legalization set by the government in accordance with the regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 12 of 2017 which was amended by regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the Land Agency. National Republic of Indonesia Number 6 of 2018 concerning Acceleration of Complete Systematic Land Registration. In 2021, the target number of land parcels to be certified is 20,000 parcels, but only 9,963 land certificates have been realized or around 49%. The problem that occurs in this research is that public services carried out by the Pekanbaru City National Land Agency office do not achieve the targets that have been set in the 2021 fiscal year. The research approach used is a qualitative approach and the type of research used is descriptive. The location of this research was conducted in Pekanbaru City and data collection techniques were carried out by interview and documentation. The results of this study are that the first public services carried out by the Pekanbaru City BPN office are not optimal, as evidenced by the failure to achieve the target of land certificates produced by the Pekanbaru City BPN Office, it is found that there is a lack of human resources that serve as a task force tasked with completing the PTSL program. Starting from the adjudication task force, juridical task force, physical task force and administrative task force. Keywords: Public Service, Land Legalization, PTSL